Measuring air layer volumes retained by submerged floating-ferns Salvinia and biomimetic superhydrophobic surfaces - Mayser, Matthias J.; Bohn, Holger F.; Reker, Meike; Barthlott, Wilhelm (Beilstein Journal of Nanotechnology, 2014)
Some plants and animals feature superhydrophobic surfaces capable of retaining a layer of air when submerged under water. Long-term air retaining surfaces (Salvinia-effect) are of high interest for biomimetic applications like drag reduction in ship coatings of up to 30%. Here we present a novel method for measuring air volumes and air loss under water. We recorded the buoyancy force of the air layer on leaf surfaces of four different Salvinia species and on one biomimetic surface using a highly sensitive custom made strain gauge force transducer setup. The volume of air held by a surface was quantified by comparing the buoyancy force of the specimen with and then without an air layer. Air volumes retained by the Salvinia-surfaces ranged between 0.15 and 1 L/m2 depending on differences in surface architecture. We verified the precision of the method by comparing the measured air volumes with theoretical volume calculations and could find a good agreement between both values. In this context we present techniques to calculate air volumes on surfaces with complex microstructures. The introduced method also allows to measure decrease or increase of air layers with high accuracy in real-time to understand dynamic processes.
Keywords: air layer; biomimetic; drag reduction; functional surfaces; plastron; Salvinia effect; volume measurement